Blue patents: expanding the scope of industrial property to foster the blue economy in Brazil - Santos, José Wendel dos; Dias, Leonôra Virginia de Jesus; Rezende, Cristiane Monteiro de Farias; Barreto Netto, José; Santos, Clara Angélica dos; De Paula, Marcelo; Dias, Cristiane Toniolo (Brazilian Journal of Production Engineering, 2025)
Sustainable innovation depends on the ability to identify and organize strategic technologies, with green patents playing a fundamental role in this process. However, the National Institute of Industrial Property (INPI) does not explicitly address aquatic technologies, leaving these innovations classified under general green technologies. This study proposes the creation of a “Blue Patents” category to classify technologies related to the Blue Economy in Brazil. The research employed an exploratory, cross-sectional, mixed-methods design based on documentary analysis. After screening, 237 patent applications related to the Blue Economy, filed between 1984 and 2024 with Brazil as the priority country, were selected and analyzed using descriptive statistics. The results showed consistent growth in patent filings over the years and revealed gaps in patent classification. While green technologies focus on terrestrial and atmospheric solutions, blue technologies address specific challenges in aquatic environments. Thus, the “Blue Patents” category could increase the visibility of these technologies, guide investment, and facilitate their dissemination to society. This study contributes to improving the Brazilian system, further aligning it with international sustainability standards.
Keywords: Patents; Blue Economy; Aquatic Technologies; Sustainable innovation